PENGARUH INDEPENDENSI, PROFESIONALISME, KETIDAKJELASAN PERAN, GAYA KEPEMIMPINAN,DAN PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA AUDITOR (Studi Empiris pada Badan Pemeriksa Keuangan RI Pusat ) - Syaftyani Anesia; Rasuli M; L Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The aim of this study was to examine the effect of Independence,Professionalism, Role Ambiguity, Leadership Style, and Good GovernanceComprehension on The Performance of Auditors. Study on suprime audit agencyRI. The respondent are in the analysis were 74 respondents (79,57%). The studyused primary data which was obtained from the answer of the respondents andthe questionnaire distributed. The collected data was analyzed using data analysismethod by firstly proposing the classical assumption before performing thehypothesis test. Classical assumption test and hypothesis test was done usingSPSS software version 23 for Windows. The hypothesis test in this research usedmultiple regression linier with t-test at significance level 5 % (α = 0 ,0 5) anddetermination coefficient test. The result of this study found that independence,professionalism, leadership style, and good governance comprehension have asignificant effect on the performace of auditors. While role ambiguity have nosignificant effect on the performance of auditors. Based on total adjusted RSquare result is 73,2%, it means Performance of Auditors (Y) can be explained bythe variable Independence (X1), Professionalism (X2), Role Ambiguity (X3),Leadership Style (X4), and Good Governance Comprehension (X5). While 26,8%is explained by other variables that were not performed in this study.Keywords : Independence, Professionalism, Role Ambiguity, Leadership Style,Good Governance Comprehension, Performance of Auditors.